Vibration response characteristics of a dual-rotor with unbalance-misalignment coupling faults: Theoretical analysis and experimental study. (July 2018) - Wang, Nanfei; Jiang, Dongxiang
Highlights: The dual-rotor dynamic model with unbalance-misalignment is developed. The complicated vibration responses are analyzed by the cascade plot, time waveform and frequency spectrum. The effects of different rotational angular speeds, mass eccentricity, misalignment angle and parallel misalignment on dynamic characteristics are investigated. The dual-rotor test rig is used to verify the proposed model. Abstract: In order to improve energy efficiency and compact structure, the dual-rotor structure, with low-pressure rotor and high-pressure rotor, has been widely used in aero-engines. In severe operation conditions, the high rotating speed dual-rotor structure is vulnerable to some faults, such as misalignment, which may cause strong vibration and even catastrophic accidents. Perfect balance of the dual-rotor system cannot be obtained in practice, and some amount of unbalance is almost always present. The rotors' centrelines are not co-linear in the couplings and the rotors run in improper axial positions in a dual-rotor system. The differential equations of rotor system is derived by using modern nonlinear dynamics and dual-rotor dynamics principles. The governing equations of the dual-rotor system with unbalance-misalignment coupling faults are solved numerically by the Runge–Kutta method. The complicated vibration responses influenced by different rotational angular speeds, mass eccentricity, misalignment angle and parallel misalignment are analyzed by the cascade plot, time waveform and frequency spectrum. Second harmonic frequency and rotational frequency components of dual rotors are observed. To verify the validity of the dual-rotor system dynamic model, the unbalance-misalignment coupling faults are carried out on a dual-rotor test rig by adjusting the height and quantity of gaskets and installing a screw on the disk of the inner rotor. The simulation results are found to agree with the experimental results. These results provide important theoretical and engineering references for the safe operation of dual-rotor system and the exact identification of coupling faults.